Freud’s ethical quandaries: psychoanalysis, existence and death - Figueroa, Gustavo (Acta Bioethica, 2020)
Freud did not make a critique of foundations of ethics nor prescribed duties, prohibitions, aspirations or alternative answers to unchanged questions, but he gave a new manner of asking moral questions. There are three areas in which Freud implied an ethic that maintains a different direction from current bioethics.1. The fundamentally nonethical character of Freud´s psychoanalysis is not included in the techniques of domination or indoctrination but of veracity, what is at stake is selfrecognition, misunderstanding is the necessary path to understanding. 2. The final position of Freud himself to his own death can be called appropriation of his finitude, when he assumed his being-unto-death, not as a being-at-his-end, indicating thereby that he understood that the end always penetrated his whole existence. 3. In the authentic comprehension of his self, Freud understood that the ultimate potentiality of his existence was to relinquish his self, he revealed to his self his potentiality for non-potentiality, becoming free for his own end, he accepted his existence in its finitude.